The influence of negotiation approaches on supplier relationship management in Zimbabwe's fast-food industry - Mukucha, Paul (Logistics, supply chain, sustainability and global challenges, 2024)
Supplier Relationship Management (SRM) has become a cornerstone of business success since the transformation of the procurement function to supply chain management. Extant literature has documented various predictors of vibrant supplier relationships. However, missing in the extant literature is the potential of negotiation approaches to cultivation of healthy supplier relationships. This study therefore sought to determine the influence of negotiation approaches on SRM. A sample of 150 dyadic transactions in the fast-food restaurant industry was surveyed. The broad dichotomous categorisation of negotiation methods into distributive and integrative approaches was used. SRM was operationalised using dimensions such as commitment, trust, communication, adaptation, and satisfaction. After conducting a Multivariate Analysis of Variance (MANOVA) the results revealed that the distributive strategy was weakly linked to supplier relationship, while a strong supplier relationship was observed in the use of integrative negotiation strategy. It was therefore recommended that procurement practitioners must employ integrative negotiation strategies and tactics in order to create sustainable supplier relationship management.
Keywords: distributive negotiation; distributivna pogajanja; fast-food industry; industrija hitre prehrane; integrative negotiation; integrativna pogajanja; supplier relationship management; upravljanje odnosov z dobavitelji